COMPETENCIES OF PUBLIC RELATIONS PERSONNEL IN THE DIGITAL AGE: A STUDY OF GOVERNMENT AGENCIES IN WEST KALIMANTAN - Pujiningsih, Herilasti (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
The development of digital technology has changed the government's public communication pattern and demands an increase in the competence of public relations personnel in managing digital media-based communication. This research aims to analyze the competencies and practices of digital public relations in government agencies in West Kalimantan, as well as identify challenges and opportunities to strengthen public relations in the digital era. The research uses a qualitative approach with a case study design in five government agencies, namely Tanjungpura University, Pontianak State Polytechnic, West Kalimantan Regional Police, Singkawang Resort Police, and Kubu Raya Regency Communication and Information Service. Data collection was carried out through in-depth interviews, observations of digital media management, and analysis of documentation and social media content. The results of the study show that the level of competence and maturity of digital PR between agencies varies. The West Kalimantan Police and the Pontianak State Polytechnic show that digital public relations practices are relatively more adaptive and structured, while other agencies still face limitations in terms of human resources, digital training, and creative content development. In general, digital public relations management still tends to be informative and one-way, with a level of public interaction that is not optimal. This study concludes that strengthening human resource competence, institutional support, and creative and participatory digital communication strategies are the main keys in increasing the effectiveness of government public relations in the digital era.